2011
DOI: 10.1038/onc.2011.8
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo pathway transcriptional co-activator, YAP, is an ovarian cancer oncogene

Abstract: The Salvador-Warts-Hippo (SWH) pathway was first discovered in Drosophila melanogaster as a potent inhibitor of tissue growth. The SWH pathway is highly conserved between D. melanogaster and mammals, both in function and in the mechanism of signal transduction. The mammalian SWH pathway limits tissue growth by inhibiting the nuclear access and expression of the transcriptional co-activator, Yes-associated protein (YAP). Mutation and altered expression of SWH pathway proteins has been observed in several types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
235
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(250 citation statements)
references
References 49 publications
11
235
0
4
Order By: Relevance
“…Huang et al reported that knockdown of YAP significantly increased EGFRI erlotinib sensitivity in ovarian cancer cell lines that express little or no TAZ (21). In addition, knockdown of YAP in ovarian cancer cell lines that express both YAP and TAZ only led to a very moderate effect on cancer cell growth or drug sensitivity (22,23). Here, we have shown that knockdown of TAZ in breast cancer cell lines that express little or no YAP, such as BT-549 cells, increased EGFRI sensitivity; however, for breast cancer cell lines that express both YAP and TAZ, such as MDA-MB-231 cells, knockdown of TAZ may not help improve sensitivity of EGFRI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al reported that knockdown of YAP significantly increased EGFRI erlotinib sensitivity in ovarian cancer cell lines that express little or no TAZ (21). In addition, knockdown of YAP in ovarian cancer cell lines that express both YAP and TAZ only led to a very moderate effect on cancer cell growth or drug sensitivity (22,23). Here, we have shown that knockdown of TAZ in breast cancer cell lines that express little or no YAP, such as BT-549 cells, increased EGFRI sensitivity; however, for breast cancer cell lines that express both YAP and TAZ, such as MDA-MB-231 cells, knockdown of TAZ may not help improve sensitivity of EGFRI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 The COSMIC data base shows an intriguing upregulation of YAP and TAZ factors in endocrine cancers (thyroid, breast, ovary and prostate). 20,21 The Drosophila homologue of YAP and TAZ is Yorkie whose overactivation also results in overgrowth. 22 Cell death during metamorphosis is considered a suitable model to investigate the basic mechanisms of tumor growth regulation by mammalian steroids.…”
mentioning
confidence: 99%
“…YAP, a mammalian homolog of Drosophila Yorkie), a key effector of this pathway, promotes EMT and cell motility in vitro (Overholtzer et al 2006;Zhao et al 2008a;Zhang et al 2009). Furthermore, abnormal YAP activity associates with poor survival of ovarian cancer patients significantly (Hall et al 2010;Zhang et al 2011b). These results drew our attention to investigate roles of the Hippo pathway in cell migration.…”
mentioning
confidence: 99%